Groundwater Modeling & Risk Management Impact of Groundwater Extraction on land Subsidance in Sarir Area East Central Libya - Nabila A. Altuwibi; Salem M. Rashrash (The Libyan Journal of Science, 2024)
This research was conducted to study the impact of exploiting groundwater on ground subsidence in Sarir water well fields, East central Libya. There are three major water well fields in this area. Known as North and South Sarir agriculture projects, they are operating since 1975, each has 239 drilled water wells at depths of 300 meters , used for irrigating of 100 hectares. the third well field belongs to the Man-made River Project, where 126 production wells(1MM3/day) drilled at depths 450m, they were operating since 1992. A comprehensive amount of data were collected on groundwater abstraction and water levers monitoring program Data such as well discharge and the drawdowns were made available for 63 observation wells covering the area of the well fields. There are two main aquifers in the area, the upper (shallow) aquifer with thickness about 150 meters and the deep aquifer is about 800 meters. These two aquifers are frequently separated with about 50m lentecular layers of clay and silt.All possible collected hydrogeological data were prepared in order to be used and build a conceptual and numerical groundwater model. This process should lead to understand the hydraulic behavior of the groundwater system in the whole area of study. The model was used to correlate the calculated hydraulic parametrs with the observed for calibration and verification. The model was also used to predict the future drawdown and land surface subsidence exerted, due to stresses forced by the long period groundwater abstractions from the three well fields.The total extracted water is 6.872 bm3since the start of the welfields to the end of 2012. The results obtained from matching the observed drawdowns with the model predictions are as follows: Specific yield and Storage Coefficient obtained from this model ranges from 0.003 to 0.12 and from 4x10-7 to 4x10-3respectively, elastic skeletal specific storage from 4x10-7 to 5x10-2, and inelastic skeletal specific storage for thin interbeds is in the range from 4x10-5 to 5x10-1. The model then used to predict the drawdown and landsubsidence after 50 years of existing and planned exploitation. The maximum drawdown is predicted to be 55meters with land surface subsidence of 2.8 meters.